APPLICATION FOR BEGINNERS GUITAR BASIC CHORD USING MACROMEDIA FLAH - Idham Adriansyah; Ire Puspa Wardhani, S.Kom.,MMSI (Jurnal Sistem Informasi, 2005)
Guitar Chord Making Applications Using Macromedia's Flash MX is a guitar chordapplication which contains information on how to search for basic chords usingMacromedia Flash MX, which is packed into an attractive and interactive form madeits appearance simple and easy. Expected that this application can help the beginnerwho wants to understand the basics of playing guitar and seek additional informationabout the search for the basic chord.By using Mcromedia Flash MX, this application is the combination of layers andelements of the picture frames, text and songs, which are summarized into a singleapplication into a form that is expected to easily be used by anyone and is made asattractive as possible while using this application.By simply clicking on one option from the menu then the user will immediatelyobtain information on the basic guitar chords.